Skeletal Muscle Mitochondrial Bioenergetics and Morphology in High Fat Diet Induced Obesity and Insulin Resistance: Focus on Dietary Fat Source - Putti, Rosalba; Migliaccio, Vincenzo; Sica, Raffaella; Lionetti, Lillà (Frontiers in Physiology, 2016)
It has been suggested that skeletal muscle mitochondria play a key role in high fat diet induced insulin resistance. Two opposite views are debated on mechanisms by which mitochondrial function could be involved in skeletal muscle insulin resistance. In one theory, mitochondrial dysfunction is suggested to cause intramyocellular lipid accumulation leading to insulin resistance. In the second theory, excess fuel within mitochondria in the absence of increased energy demand stimulates mitochondrial oxidant production and emission, ultimately leading to the development of insulin resistance. Noteworthy, mitochondrial bioenergetics is strictly associated with the maintenance of normal mitochondrial morphology by maintaining the balance between the fusion and fission processes. A shift towards mitochondrial fission with reduction of fusion protein, mainly mitofusin 2, has been associated with reduced insulin sensitivity and inflammation in obesity and insulin resistance development. However, dietary fat source during chronic overfeeding differently affects mitochondrial morphology. Saturated fatty acids induce skeletal muscle insulin resistance and inflammation associated with fission phenotype, whereas ω-3 polyunsaturated fatty acids improve skeletal muscle insulin sensitivity and inflammation, associated with a shift toward mitochondrial fusion phenotype. The present minireview focuses on mitochondrial bioenergetics and morphology in skeletal muscle insulin resistance, with particular attention to the effect of different dietary fat sources on skeletal muscle mitochondria morphology and fusion/fission balance.